Mesoporous Silica Coated Single-Walled Carbon Nanotubes as a Multifunctional Light-Responsive Platform for Cancer Combination Therapy - Liu, Jingjing; Wang, Chao; Wang, Xiaojing; Wang, Xin; Cheng, Liang; Li, Yonggang; Liu, Zhuang (Advanced functional materials, 2015)
The development of cancer combination therapies, many of which rely on nanoscale theranostic agents, has received increasing attention in recent years. In this work, polyethylene glycol (PEG) modified mesoporous silica (MS) coated single‐walled carbon nanotubes (SWNTs) are fabricated and utilized as a multifunctional platform for imaging guided combination therapy of cancer. A model chemotherapy drug, doxorubicin (DOX), could be loaded into the mesoporous structure of the obtained SWNT@MS‐PEG nano‐carriers with high efficiency. Upon stimulation under near‐infrared (NIR) light, photothermally triggered drug release from DOX loaded SWNT@MS‐PEG is observed inside cells, resulting in a synergistic cancer cell killing effect. As revealed by both photoacoustic (PA) and magnetic resonance (MR) imaging, we further uncover efficient tumor accumulation of SWNT@MS‐PEG/DOX after intravenous injection into mice. In vivo combination therapy using this agent is further demonstrated in a mouse tumor model, achieving a remarkable synergistic anti‐tumor effect superior to that obtained by mono‐therapy. Our work presents a new type of theranostic nano‐platform, which could load therapeutic molecules with high efficiency, be responsive to external NIR stimulation, and at the same time serve as a diagnostic imaging agent. Mesoporous silica coated single‐wall carbon nanotubes with polyethylene glycol functionalization and anti‐cancer drug loading are developed as a multifunctional theranostic platform. Upon systemic administration of such nano‐agent, combined photothermal and chemotherapy, which is under the guidance of multimodal magnetic resonance and photoacoustic imaging, is conducted on an animal tumor model, achieving a great synergistic therapeutic effect.